The Process of Technological Innovation in Islamic Universities: E-Campus Application at Islamic Institute of Bunga Bangsa Cirebon - Fitri Meliani Meliani; Supiana Supiana; Qiqi Yuliati Zaqiah (Program Studi Pendidikan Islam Institut Pesantren KH Abdul Chalim Mojokerto, 2022)
The use of management information systems in Islamic higher education is one of the efforts that can be made to improve the quality of education. This article aims to describe the innovation of e-campus services used by the Campus of the Islamic Institute of Bunga Bangsa Cirebon to make it easier for all elements of the campus community to access all information and academic services through one door. This research uses a qualitative approach with a descriptive method. The data collection technique is by conducting interviews and collecting several references. The interview was conducted on the subjects studied, namely the Rector, Vice-Chancellor for Curriculum, and IT Operator of the IAI BBC campus, by SWOT analysis to capture information about the mechanism for using the e-campus Information Technology application at IAI BBC. The results of this study describe the e-campus applications used at THE BBC IAI including the services of (1) PPDB; (2) Lectures; (3) Administration; (4) Data management of students and lecturers. The e-campus application is a platform that provides menus for the learning process (academic) and non-academic. The use of e-learning through the IAI Bunga Bangsa Cirebon e-campus is a combination of face-to-face (offline) with online (online) or concluded as blended learning. This learning stands on an information technology infrastructure and can be accessed anytime and anywhere that has open source characteristics for all users.